Milton Rogovin papers - Rogovin, Milton, 1909-2011.
Correspondence, draft of autobiography and other writings, interviews, FBI file, printed matter, and other papers relating to Rogovin's career as a photographer. Documents his photography of working people around the world and the working-class neighborhoods of Buffalo, N.Y., as well as the political activism underlying his work. Includes material pertaining to his exhibitions and publications. Correspondents include Margaret Taylor Burroughs, Harry M. Caudill, Robert Coles, Ossie Davis, Ruby Dee, Robert J. Doherty, W.E.B. Du Bois, Stephen Jay Gould, Grace M. Mayer, Pablo Neruda, Paul Strand, Minor White, and Rogovin's wife, Anne Rogovin, and his daughter, Ellen Rogovin Hart.
Library of Congress Prints and Photographs Division.
Social documentary photographer.
Collection material in English, with Spanish, Russian, German, Finnish and Czech.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Burroughs, Margaret Taylor, -- 1915-2010 -- Correspondence; Caudill, Harry M., -- 1922-1990 -- Correspondence; Coles, Robert -- Correspondence; Davis, Ossie -- Correspondence; Dee, Ruby -- Correspondence; Doherty, Robert J., -- 1924- -- Correspondence; Du Bois, W. E. B. -- 1868-1963 -- Correspondence; Gould, Stephen Jay -- Correspondence; Hart, Ellen Rogovin -- Correspondence; Mayer, Grace M. -- Correspondence; Neruda, Pablo, -- 1904-1973 -- Correspondence; Rogovin, Anne -- Correspondence; Strand, Paul, -- 1890-1976 -- Correspondence; White, Minor -- Correspondence; Documentary photography; Documentary photography -- New York (State) -- Buffalo; Photography -- Political aspects; Photography -- Social aspects; Buffalo (N.Y.) -- History; Buffalo (N.Y.) -- Social conditions; New York (State) -- Social conditions; Photographers